MicroRNA 92b-3p regulates primordial follicle assembly by targeting TSC1 in neonatal mouse ovaries. Issue 8 (18th April 2019) - Li, Tingting; Liu, Xiaoqiu; Gong, Xuefeng; E, Qiukai; Zhang, Xiaoqian; Zhang, Xuesen
ABSTRACT: The primordial follicle pool, providing all oocytes available to a female throughout her reproductive life, is established perinatally. The formation of primordial follicle pool is regulated by precise transcriptional and post-transcriptional mechanisms. Recent studies have identified several microRNAs as post-transcriptional regulatory factors in the process of primordial follicle assembly. Here, we showed that miR-92b-3p was significantly upregulated in the stage of primordial follicle assembly in newborn mouse ovaries. Inhibiting miR-92b-3p suppressed the formation of primordial follicles, while overexpression of miR-92b-3p accelerated the processes of cyst breakdown and the following primordial follicle assembly. Accordingly, the expression of follicular development-related genes was reduced upon inhibiting of miR-92b-3p and increased under miR-92b-3p overexpression. Mechanistic studies identified TSC1 as a direct target of miR-92b-3p. miR-92b-3p could activate mTOR/Rps6 signaling through targeting and inhibiting TSC1 expression. In addition, knockdown of TSC1 showed an identical phenotype with that of miR-92b-3p overexpression in accelerating processes of cyst breakdown and primordial follicle formation. Thus, our work demonstrates that miR-92b-3p is a novel regulator of primordial follicle assembly by negatively regulating TSC1 in mTOR/Rps6 signaling.